Comparative morpho-anatomy of Medinilla magnifica Lindl. and Medinilla sp. (Melastomataceae) - JAN LORIE, ROBIL (Archīum Ateneo, 2013)
Medinilla Gaud. (Melastomataceae) is a genus of tropical plants that has been extensively studied in terms of taxonomy and systematics. However, information about its functional morpho-anatomy is very limited. This study aimed to compare the morpho-anatom